2008
DOI: 10.1007/s11605-008-0624-6
|View full text |Cite
|
Sign up to set email alerts
|

Management of Preoperatively Suspected Choledocholithiasis: A Decision Analysis

Abstract: LCBDE has lower morbidity and mortality rates compared to preoperative ERCP/ES in the management of patients with suspected CBD stones even if the chance of CBD stones reaches 100%. Using a common duct double-lumen catheter may be considered if LCBDE is not feasible and the chance of CBD stone is less than 65%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
47
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(50 citation statements)
references
References 33 publications
2
47
0
1
Order By: Relevance
“…28 CBD stones are responsible for considerable morbidity and mortality from complications including pancreatitis, cholangitis and hepatic dysfunction. To prevent such complications, some authors recommend routine intra-operative cholangiogram to exclude unsuspected CBD stones, while undertaking laparoscopic cholecystectomy.…”
Section: Discussionmentioning
confidence: 99%
“…28 CBD stones are responsible for considerable morbidity and mortality from complications including pancreatitis, cholangitis and hepatic dysfunction. To prevent such complications, some authors recommend routine intra-operative cholangiogram to exclude unsuspected CBD stones, while undertaking laparoscopic cholecystectomy.…”
Section: Discussionmentioning
confidence: 99%
“…Hamad et al performed a retrospective analysis of 2714 adult cases, of these cases only 0.18% (n=5) required surgical intervention of bile duct injury. Efficacy and safety of OTC has also been brought into question, with a decision analysis by Kharbutli et al demonstrating the increased risk of morbidity and mortality for LC following a positive OTC [18]. In a systematic review by Metcalfe et al of 4209 LC procedures in adults, the total false positive rate of OTC was encouragingly low, at 0.8% (n=34); however, the researchers suggested that R-OTC promotes the unnecessary instrumentation of patients, as 25% of asymptomatic CBD stones have been shown to pass through the sphincter of Oddi in the interim between OTC and post-operative ERCP [19].…”
Section: Discussionmentioning
confidence: 99%
“…In these cases the use of methods to achieve stone fragmentation increases the effectiveness of LCBDE. 1,2 The first experience using laser lithotripsy for the treatment of bile duct stones is attributed to Orii et al 12 in 1983, who reported 8 patients with intrahepatic stones and 3 patients with choledocholithiasis treated with an yttriumaluminum-garnet laser. The procedure was performed shortly after the ineffectiveness of the endoscopic treatment was shown.…”
Section: Discussionmentioning
confidence: 99%
“…When ERCP is inefficient because of intrahepatic or large impacted stones in the bile duct, the next step is surgical exploration of the biliary tract. 1 We have shown the effectiveness of laparoscopy in the management of choledocholithiasis. In patients in whom ERCP is ineffective, the laparoscopic conversion rate increases mainly because of impacted stones that require complex management.…”
Section: Introductionmentioning
confidence: 98%